Cardiac Output Assessments in Anesthetized Children: Dynamic Capnography Versus Esophageal Doppler. (March 2022) - Karlsson, Jacob; Svedmyr, Anders; Wiegele, Marion; Lönnqvist, Per-Arne; Wallin, Mats; Hallbäck, Magnus
Abstract : BACKGROUND: The objective of this study was to compare esophageal Doppler cardiac output (COEDM ) against the reference method effective pulmonary blood flow cardiac output (COEPBF ), for agreement of absolute values and ability to detect change in cardiac output (CO) in pediatric surgical patients. Furthermore, the relationship between these 2 methods and noninvasive blood pressure (NIBP) parameters was evaluated. METHODS: Fifteen children American Society of Anesthesiology (ASA) I and II (median age, 8 months; median weight, 9 kg) scheduled for surgery were investigated in this prospective observational cohort study. Baseline COEPBF /COEDM /NIBP measurements were made at positive end-expiratory pressure (PEEP) 3 cm H2 O. PEEP was increased to 10 cm H2 O and COEPBF /COEDM /NIBP was recorded after 1 and 3 minutes. PEEP was then lowered to 3 cm H2 O, and all measurements were repeated after 3 minutes. Finally, 20-µg kg −1 intravenous atropine was given with the intent to increase CO, and all measurements were recorded again after 5 minutes. Paired recordings of COEDM and COEPBF were examined for agreement and trending ability, and all parameters were analyzed for their responses to the hemodynamic challenges. RESULTS: Bias between COEDM and COEPBF (COEDM − COEPBF ) was −17 mL kg −1 min −1 (limits of agreement, −67 to +33 mL kg −1 min −1 ) with a mean percentage error of 32% (95% confidence interval [CI], 25–37) and a concordance rate of 71% (95% CI, 63–80). The hemodynamic interventions caused by PEEP manipulations resulted in significant decrease in COEPBF absolute numbers (155 mL kg −1 min −1 [95% CI, 151–159] to 127 mL kg −1 min −1 [95% CI, 113–141]) and a corresponding relative decrease of 18% (95% CI, 14–22) 3 minutes after application of PEEP 10. No corresponding decreases were detected by COEDM . Mean arterial pressure showed a relative decrease with 5 (95% CI, 2–8) and 6% (95% CI, 2–10) 1 and 3 minutes after the application of PEEP 10, respectively. Systolic arterial pressure showed a relative decrease of 5% (95% CI, 2–10) 3 minutes after application of PEEP 10. None of the recorded parameters responded to atropine administration except for heart rate that showed a 4% relative increase (95% CI, 1–7, P = .02) 5 minutes after atropine. CONCLUSIONS: COEDM was unable to detect the reduction of CO cause by increased PEEP, whereas COEPBF and to a minimal extent NIBP detected these changes in CO. The ability of COEPBF to react to minor reductions in CO, before noticeable changes in NIBP are seen, suggests that COEPBF may be a potentially useful tool for hemodynamic monitoring in mechanically ventilated children.